2020
DOI: 10.3329/jsr.v12i4.45389
|View full text |Cite
|
Sign up to set email alerts
|

Topological Indices of Dendrimers used in Drug Delivery

Abstract: The topological index is a numerical representation of a molecular structure. In chemical graphs, the atoms and the chemical bonds between them are represented by vertices and edges respectively. Vertex degree based topological indices are the most studied and mostly used type of topological indices. The mostly used vertex degree based topological indices in the field of drug design and developments are the Zagreb index and the Randić index. The structural chemistry of dendrimers could be manipulated by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The Randić index and the Zagreb index are the mostly studied types of degree-based topological indices in drug design (Gao et al, 2013: Nilanjan De, 2018Jude et al, 2019;Jude et al, 2020). The well-known Zagreb index which is the oldest degree-based topological index was introduced by Gutman and Trinajstić in 1972 during the analysis of the structure-dependency of total π-electron energy (Gutman & Trinajstić, 1972).…”
Section: {��}⊆�(�)mentioning
confidence: 99%
“…The Randić index and the Zagreb index are the mostly studied types of degree-based topological indices in drug design (Gao et al, 2013: Nilanjan De, 2018Jude et al, 2019;Jude et al, 2020). The well-known Zagreb index which is the oldest degree-based topological index was introduced by Gutman and Trinajstić in 1972 during the analysis of the structure-dependency of total π-electron energy (Gutman & Trinajstić, 1972).…”
Section: {��}⊆�(�)mentioning
confidence: 99%
“…Also, Rajeswari and Parvathi discussed the Zagreb indices correlating nanotubes [18] and detailed studies on nanotechnology can be found from studies [19,20]. The application relating drug delivery and topological indices provides a key role in COVID-19 treatment [21][22][23][24][25]. Ortega et al gave a brief explanation on MATLAB based particle size distribution to understand the physical properties of compounds [26].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they help in the study of certain physical characteristics of chemical compounds such as the boiling point, ash point, density, stability, and many more. They also serve as powerful tools to execute biological network analysis, and also to determine the physical features and the chemical reactions associated with various drugs without having to carry out the actual experiment, for instance, see [15,16].…”
Section: Introductionmentioning
confidence: 99%